Students as assessors - Mat Daud, Nuraihan; Abu Kassim, Noor Lide (IIUM Press, International Islamic University Malaysia, 2011)
One important educational objective is to produce students who are critical of their own learning. A way this can be achieved is by giving students a more active role in the assessment process. This study examines the possibility of having students as assessors of their own performance. The study was conducted at the International Islamic University Malaysia in Computer Applications in Language Studies classes where problem-based learning approach was adopted. Ratings given by three categories of assessors namely teacher, self, and peer on two oral presentations were compared to see whether there were inconsistencies in the rating behavior of the different groups of assessors. Both quantitative and qualitative techniques were used in data collection. All assessors used the same assessment profile. Diary entry and interview techniques were used to gain further insight into students' rating behavior. The quantitative data were analyzed using the Many-facet Rasch model and results show that there were significant differences in the quality of ratings given by the three groups.Different levels of severity/leniency were observed when the two tasks were analyzed. The study also looked at the level of difficulties of the criteria used in the assessment procedure. The findings indicate that there were significant differences in the difficulty level of the criteria used. The diary entries and interviews conducted at the end of the semester revealed that students had Language Studies in the Muslim World reservations about having wassess themselves. This was supported by the slight inconsistency in students' ratings and the leniency of the self-'ratings. On the other hand, ratings given by peers were found will be more consistent and more severe.